2022
DOI: 10.1002/hpja.618
|View full text |Cite
|
Sign up to set email alerts
|

Procurement from local producers for food service in primary and secondary school settings: A scoping review

Abstract: Issue addressed: Australian school canteen guidelines do not broadly incentivise procuring food from local producers, despite evidence of this occurring abroad. This scoping review aims to investigate what is known about local food procurement for school foodservice.Methods: A scoping review of peer-reviewed articles published since 2000 was undertaken using MEDLINE, CINAHL and Scopus.Results: Twenty-one studies met the inclusion criteria. Local food was generally perceived as fresher and more nutritious. Smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Given our main findings, we share only partially the enthusiasm that prevails in most discourses and in recent reviews (Filippini et al, 2018;Long et al, 2021;Molin et al, 2021;Galloway et al, 2022;Xie et al, 2022) which frequently omit to assess the links between school food relocalization and regional crop and farm diversification. Certainly, school food catering actors managed to channel a higher share of sustainable products to meet legal requirements, opening significant market opportunities.…”
Section: Discussionmentioning
confidence: 52%
“…Given our main findings, we share only partially the enthusiasm that prevails in most discourses and in recent reviews (Filippini et al, 2018;Long et al, 2021;Molin et al, 2021;Galloway et al, 2022;Xie et al, 2022) which frequently omit to assess the links between school food relocalization and regional crop and farm diversification. Certainly, school food catering actors managed to channel a higher share of sustainable products to meet legal requirements, opening significant market opportunities.…”
Section: Discussionmentioning
confidence: 52%
“…The use of locally and seasonally grown goods was in the present study found to be valued by many municipalities, notably to diminish "food miles" and support local economies, including small and local-regional farmers, traditions and culture in food production, as well as ensuring diversity in food products. Likewise, a recently published review on local food procurement policies and practices in primary and secondary school food service found that perhaps the most common initiator or motivation for participating in local food procurement is a sense of social responsibility [45].…”
Section: Local and Seasonal Foodmentioning
confidence: 99%